Organic silicon adhesive, preparation method thereof and photovoltaic module

By introducing specific components and additives into the silicone adhesive, improving its bonding strength and mechanical properties, the problem of laminated parts being unframed when the load bearing is too high is solved, which significantly extends the components Service life.

CN119463801APending Publication Date: 2025-02-18TRINA SOLAR CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411681772.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the load bearing force of large-format photovoltaic modules is too high, conventional silicone adhesives are easily torn, causing the laminate to be out of frame, affecting the normal use and service life of the components.

Method used

Composites such as terminal hydroxy polydimethylsiloxane, dimethyl silicone oil, surface modified nano calcium carbonate, alkoxy modified MQ resin, etc., and a crosslinking agent, silane coupling agent and Catalyst to improve the bonding strength and mechanical properties of organic silicone adhesives.

Benefits of technology

It significantly improves the physical properties, initial mechanical strength and DH1000 after aging, enhances the bearing capacity of photovoltaic modules and extends the service life of the modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides an organic silicon adhesive, a preparation method thereof and a photovoltaic module. The organic silicon adhesive is prepared from the following components in parts by weight: 42 to 50 parts by weight of hydroxyl-terminated polydimethylsiloxane, 1 to 4 parts by weight of dimethyl silicone oil, 31 to 36 parts by weight of surface modified nano calcium carbonate, 11 to 16 parts by weight of alkoxy modified MQ resin, 3 to 4 parts by weight of a cross-linking agent, 0.4 to 0.7 part by weight of a silane coupling agent and 0.1 to 0.3 part by weight of a catalyst. The organic silicon adhesive disclosed by the scheme has relatively high bonding strength and good physical properties and mechanical properties, so that the organic silicon adhesive has excellent bearing capacity when being applied to a large-model assembly, and the service life of a photovoltaic assembly is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to an organic silicone adhesive and a preparation method thereof, and a photovoltaic module. Background Art

[0002] Organic silicone adhesive has excellent resistance to cold and heat, durability and sealing performance, and is widely used in the packaging process of photovoltaic modules. When encapsulating photovoltaic modules, organic silicone adhesive is mainly used between photovoltaic laminates and photovoltaic frames to bond the laminates to the photovoltaic frames.

[0003] In recent years, photovoltaic modules have gradually developed in the direction of high-power large-format modules. As the size of the modules increases, the modules deform significantly due to their own weight, and are more susceptible to wind loads, which leads to a significantly increased risk of tearing and falling off the laminate and frame. Therefore, in order to address the load-bearing risk of large-format modules, the performance of each material of the module needs to be improved. The organic silicone adhesive used to bond the laminate and the photovoltaic frame has the function of resisting the separation of the laminate and the frame. However, if the load-bearing force of the module is too large and the deformation of the module is large, conventional organic silicone adhesives are easily torn due to the external strength being higher than its body strength, resulting in the phenomenon of the laminate falling off the frame, affecting the normal use of the module and causing the module to fail. Summary of the invention

[0004] The present application provides an organic silicone adhesive and a preparation method thereof, and a photovoltaic module to solve or alleviate the above-mentioned technical problems. The organic silicone adhesive provided by the technical solution of the present application can better improve the load-bearing capacity of the photovoltaic module and extend the service life of the photovoltaic module.

[0005] In a first aspect, an embodiment of the present application provides an organic silicone adhesive, comprising the following components in parts by weight: 42-50 parts by weight of terminal hydroxyl polydimethylsiloxane, 1-4 parts by weight of dimethyl silicone oil, 31-36 parts by weight of surface modified nano calcium carbonate, 11-16 parts by weight of alkoxy modified MQ resin, 3-4 parts by weight of crosslinking agent, 0.4-0.7 parts by weight of silane coupling agent and 0.1-0.3 parts by weight of catalyst.

[0006] Preferably, the viscosity of the hydroxy-terminated polydimethylsiloxane is 40000-60000 mPa·s.

[0007] Preferably, the viscosity of the dimethyl silicone oil is 1000-3000 mPa·s.

[0008] Preferably, the surface-modified nano-calcium carbonate is nano-calcium carbonate surface-modified with γ-aminopropyltriethoxysilane.

[0009] Preferably, the specific surface area of ​​the surface-modified nano-calcium carbonate is 26-34 m 2 / g.

[0010] Preferably, the alkoxy-modified MQ resin is one or both of methoxy MQ resin and ethoxy MQ resin.

[0011] Preferably, the M / Q molar ratio of the alkoxy-modified MQ resin is 1.2-1.4.

[0012] Preferably, the crosslinking agent includes one or both of tetraethyl orthosilicate and methyltrimethoxysilane.

[0013] Preferably, the silane coupling agent includes one or more of N-2-aminoethyl-3-aminopropyltrimethoxysilane oligomer, 3-diethylenetriaminopropyltrimethoxysilane oligomer, and γ-(methacryloyloxy)propyltrimethoxysilane oligomer.

[0014] Preferably, the catalyst includes one or both of dimethyltin diceneodecanoate and dibutyltin bis(acetylacetonate).

[0015] Preferably, the mass ratio of the terminal hydroxyl polydimethylsiloxane to the dimethyl silicone oil is 15:1-25:1.

[0016] Preferably, the mass ratio of the surface-modified nano-calcium carbonate to the alkoxy-modified MQ resin is 1.9:1-3.3:1.

[0017] In a second aspect, an embodiment of the present application provides a method for preparing the organic silicone adhesive described in any one of the above embodiments, comprising: Stir terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil, surface modified nano calcium carbonate and alkoxy modified MQ resin for 2-4 hours in an environment with a temperature of 100-120° C. and a vacuum degree of less than or equal to -0.095 MPa to obtain a first mixture; Adding a crosslinking agent to the first mixture and stirring for 15-25 minutes to obtain a second mixture; A silane coupling agent and a catalyst are added to the second mixture, and the mixture is stirred for 20-30 minutes in an environment with a vacuum degree of -0.10 MPa to -0.09 MPa to obtain the organic silicone adhesive.

[0018] In a third aspect, an embodiment of the present application provides a photovoltaic module, comprising the organic silicone adhesive described in any of the above embodiments.

[0019] The above technical solution adopted in the embodiment of the present application may have the following advantages: The organic silicone adhesive of the present application is compounded with appropriate amounts of terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil, surface-modified nano calcium carbonate, and alkoxy-modified MQ resin, and introduces appropriate amounts of crosslinking agent, silane coupling agent, and catalyst to improve the bonding strength of the organic silicone adhesive. While ensuring that the sizing process of the organic silicone adhesive remains unchanged, its physical properties, initial mechanical strength, and mechanical strength after DH1000 aging are significantly improved, so that it has excellent load-bearing capacity when applied to large-format photovoltaic modules, greatly extending the service life of photovoltaic modules. DETAILED DESCRIPTION

[0020] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.

[0021] The present application provides an organic silicone adhesive, comprising the following components in parts by weight: 42-50 parts by weight of terminal hydroxyl polydimethylsiloxane, 1-4 parts by weight of dimethyl silicone oil, 31-36 parts by weight of surface modified nano calcium carbonate, 11-16 parts by weight of alkoxy modified MQ resin, 3-4 parts by weight of crosslinking agent, 0.4-0.7 parts by weight of silane coupling agent and 0.1-0.3 parts by weight of catalyst.

[0022] The functions and contents of each component in the organic silicone adhesive are described as follows: Hydroxyl-terminated polydimethylsiloxane is the main component of organic silicone adhesive. Its molecular chain is composed of silicon-oxygen bonds, which provides a basic three-dimensional network structure for organic silicone adhesive, and reacts chemically with crosslinking agents and silane coupling agents to form a crosslinked structure, thereby enhancing bonding strength and cohesion and improving the mechanical properties of organic silicone adhesive. A suitable amount of hydroxyl-terminated polydimethylsiloxane can have good compatibility with alkoxy-modified MQ resin, which is beneficial to the mechanical properties of organic silicone adhesive. In the organic silicone adhesive of the present application, the content of hydroxyl-terminated polydimethylsiloxane is 42-50 parts by weight, preferably 45-48 parts by weight.

[0023] Dimethyl silicone oil can improve the rheological properties of silicone adhesives and improve the extrusion properties of silicone adhesives, thereby improving the quality of silicone adhesive products. The amount of dimethyl silicone oil should not be too large, otherwise it will increase the surface drying time of the silicone adhesive and reduce the mechanical properties of the photovoltaic module; the amount of dimethyl silicone oil should not be too small, otherwise the silicone adhesive will not be able to achieve the required rheological properties. In the silicone adhesive of the present application, the content of dimethyl silicone oil is 1-4 parts by weight, preferably 2-3 parts by weight.

[0024] Surface-modified nano-calcium carbonate is a reinforcing filler that can improve the physical properties of organic silicone adhesives, enhance the hardness and wear resistance of organic silicone adhesives, and can also improve the tensile strength of organic silicone adhesives and reduce material costs. In organic silicone adhesives, if the amount of surface-modified nano-calcium carbonate is too large, the surface-modified nano-calcium carbonate particles will aggregate, affecting the mechanical properties and rheological properties of the organic silicone adhesive; if the amount of surface-modified nano-calcium carbonate is too small, its reinforcing effect cannot be exerted; therefore, the content of surface-modified nano-calcium carbonate is controlled to 31-36 parts by weight, preferably 33-35 parts by weight.

[0025] MQ resin is composed of monofunctional chain segments (R3SiO 1 / 2 M) and tetrafunctional segments (SiO 4 / 2 That is, an organic / inorganic hybrid polyorganosiloxane with a special structural ratio composed of Q). Alkoxy-modified MQ resin is a reinforcing agent for organic silicone adhesive. By introducing alkoxy functional groups, the compatibility with terminal hydroxyl polydimethylsiloxane is enhanced, thereby improving the mechanical strength of the organic silicone adhesive and making the organic silicone adhesive have good light transmittance and fluidity. In the organic silicone adhesive of the present application, the content of alkoxy-modified MQ resin is 11-16 parts by weight, preferably 12-15 parts by weight.

[0026] The crosslinking agent contains multiple functional groups and can form chemical bonds between linear or slightly branched macromolecules, crosslinking the terminal hydroxyl polydimethylsiloxane and the silane coupling agent to form a three-dimensional network structure, thereby improving the molding speed, mechanical strength, wear resistance, and high temperature resistance of the organic silicone adhesive, and improving the adsorption performance and softness of the organic silicone adhesive. If the amount of the crosslinking agent is too large, the crosslinking density of the organic silicone adhesive will be too high, making the organic silicone adhesive too hard and brittle, thereby reducing its flexibility and impact resistance; if the amount of the crosslinking agent is too small, the cohesion of the organic silicone adhesive will be reduced. In the organic silicone adhesive of the present application, the content of the crosslinking agent is 3-4 parts by weight, preferably 3.2-3.8 parts by weight.

[0027] Silane coupling agents contain silicon-hydrogen bonds. When contacting the adherend material, the silane coupling agent reacts with the adherend and the terminal hydroxyl polydimethylsiloxane through the silicon-philic group to form a strong and durable covalent bond, thereby improving the interfacial adhesion, weather resistance, chemical corrosion resistance, and improving wettability and dispersibility. Too much silane coupling agent will increase the viscosity of the organic silicone adhesive, which is not conducive to rheology; too little silane coupling agent will lead to insufficient bonding strength of the organic silicone adhesive. In the organic silicone adhesive of the present application, the content of silane coupling agent is 0.4-0.7 parts by weight, preferably 0.5-0.6 parts by weight.

[0028] The catalyst can reduce the activation energy of the reaction, thereby accelerating the curing reaction, shortening the curing time of the organic silicone adhesive, and improving the strength of the organic silicone adhesive. If the amount of catalyst is too much, it is difficult to control the reaction process, affecting the quality of the product; if the amount of catalyst is too little, the curing time cannot be controlled within a reasonable range, affecting production efficiency. In the organic silicone adhesive of the present application, the content of the catalyst is 0.1-0.3 parts by mass, preferably 0.2-0.3 parts by mass.

[0029] The organic silicone adhesive of the present application is compounded with appropriate amounts of terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil, surface-modified nano calcium carbonate, and alkoxy-modified MQ resin, and introduces appropriate amounts of crosslinking agent, silane coupling agent, and catalyst to improve the bonding strength of the organic silicone adhesive. While ensuring that the sizing process of the organic silicone adhesive remains unchanged, its physical properties, initial mechanical strength, and mechanical strength after DH1000 aging are significantly improved, so that it has excellent load-bearing capacity when applied to large-format photovoltaic modules, greatly extending the service life of photovoltaic modules.

[0030] In some embodiments, the viscosity of the hydroxy-terminated polydimethylsiloxane is 40,000-60,000 mPa·s.

[0031] The larger the molecular weight of the terminal hydroxyl polydimethylsiloxane, the higher its viscosity, which generally means that the molecular chain is longer and the interaction between molecules is stronger. Higher viscosity may help to improve the cohesion and bonding properties of the silicone adhesive, but too high viscosity will reduce its compatibility with the alkoxy-modified MQ resin, thereby affecting the performance of the silicone adhesive. When the viscosity of the terminal hydroxyl polydimethylsiloxane is 40,000-60,000 mPa·s, it has good compatibility with the alkoxy-modified MQ resin, and the silicone adhesive has better cohesion and bonding properties. Specifically, the viscosity of the terminal hydroxyl polydimethylsiloxane can be 40,000 Pa·s, 45,000 Pa·s, 50,000 mPa·s, 55,000 Pa·s or 60,000 mPa·s.

[0032] In some embodiments, the viscosity of dimethicone oil is 1000-3000 mPa·s.

[0033] In organic silicone adhesives, if the viscosity of dimethyl silicone oil is too high, it will increase the viscosity of the organic silicone adhesive, thereby affecting its fluidity and construction performance; if the viscosity of dimethyl silicone oil is too low, it will cause the bonding strength and cohesion of the organic silicone adhesive to decrease. When the viscosity of dimethyl silicone oil is 1000-3000mPa·s, the organic silicone adhesive can have both fluidity and bonding strength. Specifically, the viscosity of dimethyl silicone oil can be 1000Pa·s, 1500Pa·s, 2000mPa·s, 2500mPa·s or 3000mPa·s.

[0034] In some embodiments, the surface-modified nano-calcium carbonate is nano-calcium carbonate surface-modified with γ-aminopropyltriethoxysilane. By using the surfactant γ-aminopropyltriethoxysilane to surface-modify the nano-calcium carbonate, the affinity of calcium carbonate with silicone resin (hydroxy-terminated polydimethylsiloxane) can be significantly improved, thereby improving its dispersibility and affinity in the silicone resin, and further increasing the reinforcing effect on the silicone resin.

[0035] In some embodiments, the specific surface area of ​​the surface-modified nano-calcium carbonate is 26-34 m 2 / g. The specific surface area of ​​calcium carbonate has an important influence on the tensile strength of organic silicone adhesives. Generally, the tensile strength increases with the increase of specific surface area. However, too large a specific surface area will reduce its dispersion performance and affect the extrusion of organic silicone adhesives. When the specific surface area of ​​surface-modified nano calcium carbonate is 26-34m 2 / g, not only the extrusion performance of the organic silicone adhesive is suitable for the production line, but also the organic silicone adhesive can be guaranteed to have a high tensile strength. Specifically, the specific surface area of ​​the surface-modified nano calcium carbonate can be 26m 2 / g, 27m 2 / g, 28m 2 / g, 30m 2 / g, 31m 2 / g, 32m 2 / g, 33m 2 / g or 34m 2 / g.

[0036] In some embodiments, the alkoxy modified MQ resin is one or both of methoxy MQ resin and ethoxy MQ resin. In methoxy MQ resin and ethoxy MQ resin, since the introduced alkoxy group belongs to a small molecular group, the compatibility with terminal hydroxyl polydimethylsiloxane is better.

[0037] In some embodiments, the M / Q molar ratio of the alkoxy-modified MQ resin is 1.2-1.4. When the M / Q molar ratio of the alkoxy-modified MQ resin is within this range, the alkoxy-modified MQ resin has good compatibility with the hydroxy-terminated polydimethylsiloxane, which is conducive to the dispersion of the alkoxy-modified MQ resin in the hydroxy-terminated polydimethylsiloxane, thereby improving the physical properties of the organic silicone adhesive.

[0038] In some embodiments, the crosslinking agent includes one or both of tetraethyl orthosilicate and methyltrimethoxysilane. Both crosslinking agents are linear polymer chains formed by connecting siloxane units, and have a similar structure to terminal hydroxyl polydimethylsiloxane. Therefore, tetraethyl orthosilicate and methyltrimethoxysilane have good compatibility with terminal hydroxyl polydimethylsiloxane, which is beneficial to further improve the bonding performance of the organic silicone adhesive.

[0039] In some embodiments, when the crosslinking agent includes tetraethyl orthosilicate and methyltrimethoxysilane, the mass ratio of the two is 2:1-6:1, specifically 2:1, 3:1, 4:1, 5:1 or 6:1.

[0040] In some embodiments, the silane coupling agent includes one or more of N-2-aminoethyl-3-aminopropyl trimethoxysilane oligomer, 3-diethylenetriaminopropyl trimethoxysilane oligomer, and γ-(methacryloyloxy)propyl trimethoxysilane oligomer. These three silane coupling agents all contain amino groups and react fully with the cross-linking agent, which is beneficial to improving the bonding strength of the organic silicone adhesive.

[0041] In some embodiments, when the silane coupling agent includes N-2-aminoethyl-3-aminopropyltrimethoxysilane oligomer, 3-diethylenetriaminopropyltrimethoxysilane oligomer and γ-(methacryloyloxy)propyltrimethoxysilane oligomer, the mass ratio of the three is 2:(1-3):(1-3), specifically 2:1:1, 2:1:2, 2:1:3, 2:2:1, 2:2:2, 2:2:3, 2:3:1, 2:3:2 or 2:3:3.

[0042] In some embodiments, the catalyst includes one or both of dimethyltin dineodecanoate and dibutyltin bis(acetylacetonate). These two catalysts can significantly accelerate the curing reaction of the organic silicone adhesive, thereby improving the bonding effect.

[0043] In some embodiments, when the catalyst includes dimethyltin diceneodecanoate and dibutyltin bis(acetylacetonate), the mass ratio of the two is 1:2-2:1, specifically 1:2, 1:1 or 2:1.

[0044] In some embodiments, the mass ratio of the terminal hydroxyl polydimethylsiloxane to the dimethyl silicone oil is 15:1-25:1, preferably 18:1-22:1.

[0045] In some embodiments, the mass ratio of the surface-modified nano-calcium carbonate to the alkoxy-modified MQ resin is 1.9:1-3.3:1, preferably 2:1-3:1.

[0046] The present application embodiment provides a method for preparing an organic silicone adhesive, which is used to prepare the organic silicone adhesive described in any of the above embodiments, comprising: S100: stirring the terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil, surface-modified nano-calcium carbonate and alkoxy-modified MQ resin for 2-4 hours in an environment with a temperature of 100-120° C. and a vacuum degree of less than or equal to -0.095 MPa to obtain a first mixture; S200: adding a cross-linking agent to the first mixture and stirring for 15-25 minutes to obtain a second mixture; S300: adding a silane coupling agent and a catalyst to the second mixture, stirring for 20-30 minutes in an environment with a vacuum degree of -0.10 MPa to -0.09 MPa (-0.095 MPa), to obtain the organic silicone adhesive.

[0047] In some embodiments, the preparation method of alkoxy-modified MQ resin comprises: Dissolve 50.0 g of dried methyl vinyl MQ silicone resin in 10.0 mL of toluene at room temperature and add the mixture into a three-necked flask; Under stirring, add 12 mL of alkoxysilane and 100 μL of chloroplatinic acid catalyst into the three-necked flask; Under nitrogen atmosphere, stir with a magnetic stirrer at 40 r / min and heat to 80°C, reflux for 6 h, then heat to 100°C and distill under reduced pressure for 30 min to remove volatile substances; The material was discharged and placed in a vacuum drying oven at 80° C. for 5 h to obtain an alkoxy-modified MQ resin.

[0048] When the alkoxysilane is trimethoxysilane, the prepared alkoxy-modified MQ resin is a methoxy MQ resin; when the alkoxysilane is triethoxysilane, the prepared alkoxy-modified MQ resin is an ethoxy MQ resin.

[0049] The following specific examples further illustrate the present application in detail, but should not be construed as limiting the present application. Without departing from the spirit and substance of the present application, modifications or substitutions made to the methods, steps or conditions of the present application are within the scope of the present application. The following further lists the formulas of the organic silicone adhesives of Examples 1-14 of the present application and Comparative Examples 1-5, and the specific formulas are shown in Table 1.

[0050] Table 1

[0051] Table 1 (continued)

[0052] Table 1 (continued)

[0053] In Examples 1 to 14 of the present application, the viscosity of the hydroxy-terminated polydimethylsiloxane is 40000-60000 mPa·s, the viscosity of the dimethyl silicone oil is 1000-3000 mPa·s, and the specific surface area of ​​the surface-modified nano-calcium carbonate is 26-34 m 2 / g.

[0054] The preparation methods of Examples 1 to 14 and Comparative Examples 1 to 4 include: S110: Stir terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil, surface modified nano calcium carbonate and alkoxy modified MQ resin (if the components are not in the formula, there is no need to add the corresponding components) for 3 hours in an environment with a temperature of 110° C. and a vacuum degree of -0.095 MPa to obtain a first mixture; S210: adding a cross-linking agent to the first mixture and stirring for 20 minutes to obtain a second mixture; S310: adding a silane coupling agent and a catalyst to the second mixture, stirring for 25 minutes in an environment with a vacuum degree of -0.095 MPa, to obtain the organic silicone adhesive.

[0055]

Performance test

[0056] Table 2

[0057] Table 2 (continued)

[0058] The load test uses a large-size component with a size of 2382mm*1303mm. The front side is loaded with 5400Pa for 1h, and then the back side is loaded with 2400Pa for 1h. This is one cycle. A total of 3 cycles are tested to observe whether the component is out of the frame. At the same time, 5 components are arranged for each embodiment test to calculate the test pass rate.

[0059] From the test results in Table 1, it can be seen that the organic silicone adhesives of Examples 1-14 of the present application have good mechanical properties, with an initial tensile strength of ≥3.0 MPa, a tensile strength after DH1000 of ≥2.0 MPa, and a component load pass rate of 100% before and after environmental aging, which greatly improves the bearing capacity of the component and thus extends the service life of the component. In Examples 1-14 of the present application, terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil, surface-modified nano-calcium carbonate, and alkoxy-modified MQ resin are contained at the same time; the alkoxy MQ silicone resin (methoxy MQ silicone resin and ethoxy MQ silicone resin) has good storage stability and controllable methoxy or ethoxy content, and the special organic-inorganic structure of the methoxy MQ resin or ethoxy MQ silicone resin makes it have good compatibility with terminal hydroxyl polydimethylsiloxane, and at the same time, the surface silanol groups can condense with the silanol groups at both ends of the terminal hydroxyl polydimethylsiloxane to form a strong chemical bond, and the surface-modified nano-calcium carbonate has a reinforcing effect, which greatly improves the mechanical properties of the organic silicone adhesive; at the same time, due to the addition of dimethyl silicone oil, it is used to adjust the rheological properties of the organic silicone adhesive. The organic silicone adhesive of comparative examples 1-4 has an initial tensile strength of <3.0MPa, a tensile strength after DH1000 of <1.8MPa, and relatively low mechanical properties after aging, resulting in a load test after environmental aging that does not reach 100%, but ≤80%, with limited bearing capacity, and there are certain risks in long-term use; and the extrudability of comparative examples 1-4 is higher than that of embodiments 1-14, which is not conducive to production line use (production lines generally require 16-20s / 20g). This is because comparative examples 1 and 2 do not have surface-modified nano-calcium carbonate, which cannot effectively reinforce and connect the methoxy MQ silicone resin, and will increase the viscosity of the organic silicone adhesive, so that its mechanical properties cannot meet the requirements, and the increase in viscosity makes the extrudability of the organic silicone adhesive worse (not easy to extrude); comparative examples 3-4 contain surface-modified nano-calcium carbonate, but do not contain methoxy MQ silicone resin. Since the surface-modified nano-calcium carbonate alone cannot effectively reinforce the organic silicone adhesive, the initial strength and strength after aging of the organic silicone adhesive cannot meet the requirements.

[0060] In summary, the organic silicone adhesive of the present application is compounded with appropriate amounts of terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil, surface-modified nano-calcium carbonate, and alkoxy-modified MQ resin, and introduces appropriate amounts of cross-linking agent, silane coupling agent and catalyst to improve the bonding strength of the organic silicone adhesive. While ensuring that the sizing process of the organic silicone adhesive remains unchanged, its physical properties, initial mechanical strength, and mechanical strength after DH1000 aging are significantly improved, so that it has excellent load-bearing capacity when applied to large-format photovoltaic modules, greatly extending the service life of photovoltaic modules.

[0061] An embodiment of the present application also provides a photovoltaic module, comprising a laminate, a photovoltaic frame, and the organic silicone adhesive described in any of the above embodiments, wherein the organic silicone adhesive bonds the laminate and the photovoltaic frame to ensure the performance and quality of the photovoltaic module.

[0062] The embodiment of the present application also provides a photovoltaic system, including the photovoltaic components provided in the above embodiment. The advantages of the above photovoltaic components are also possessed by the photovoltaic system, which will not be repeated here. The above photovoltaic system has a wide range of applications, not only limited to photovoltaic power stations, such as ground power stations, rooftop power stations and water power stations, but also includes various equipment and devices that use solar energy to generate electricity, such as user solar power supplies, solar street lights, solar cars and solar buildings. Of course, it can be understood that the application scenarios of the photovoltaic system are not limited to this, that is to say, the photovoltaic system can be used in all fields where solar energy is required for power generation. Taking the photovoltaic power generation system network as an example, the photovoltaic system may include a photovoltaic array, a junction box and an inverter. The photovoltaic array may be an array combination of multiple photovoltaic components. For example, multiple photovoltaic components may form multiple photovoltaic arrays. The photovoltaic array is connected to a junction box. The junction box can converge the current generated by the photovoltaic array. The converged current flows through the inverter and is converted into the alternating current required by the mains power grid, and then connected to the mains network to realize solar power supply.

[0063] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0064] It should be noted that: in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device that includes the element.

[0065] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, please refer to the relevant description of other embodiments. The above embodiments are only used to illustrate the technical solution of the present application, rather than to limit it. Although the present application is described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that it is still possible to modify the technical solutions recorded in the aforementioned embodiments, or to replace some of the technical features therein by equivalents; and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

[0066] It should also be noted that "one embodiment", "another embodiment", "embodiment", etc. mentioned in this application refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Further, when describing a specific feature, structure or characteristic in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of this application.

Claims

1. An organic silicone adhesive, characterized in that: The composition comprises the following components in parts by weight: 42-50 parts by weight of terminal hydroxyl polydimethylsiloxane, 1-4 parts by weight of dimethyl silicone oil, 31-36 parts by weight of surface modified nano calcium carbonate, 11-16 parts by weight of alkoxy modified MQ resin, 3-4 parts by weight of crosslinking agent, 0.4-0.7 parts by weight of silane coupling agent and 0.1-0.3 parts by weight of catalyst.

2. The organic silicone adhesive according to claim 1, characterized in that: The viscosity of the hydroxy-terminated polydimethylsiloxane is 40000-60000 mPa·s; and / or The viscosity of the dimethyl silicone oil is 1000-3000 mPa·s.

3. The organic silicone adhesive according to claim 1, characterized in that: The surface-modified nano-calcium carbonate is nano-calcium carbonate surface-modified with γ-aminopropyltriethoxysilane; and / or The specific surface area of ​​the surface modified nano calcium carbonate is 26-34m 2 / g.

4. The organic silicone adhesive according to claim 1, characterized in that: The alkoxy modified MQ resin is one or both of methoxy MQ resin and ethoxy MQ resin.

5. The organic silicone adhesive according to claim 1, characterized in that: The M / Q molar ratio of the alkoxy-modified MQ resin is 1.2-1.

4.

6. The organic silicone adhesive according to any one of claims 1 to 5, characterized in that: The crosslinking agent includes one or both of tetraethyl orthosilicate and methyltrimethoxysilane; and / or The silane coupling agent includes one or more of N-2-aminoethyl-3-aminopropyltrimethoxysilane oligomer, 3-diethylenetriaminopropyltrimethoxysilane oligomer, and γ-(methacryloyloxy)propyltrimethoxysilane oligomer; and / or The catalyst includes one or two of dimethyltin diceneodecanoate and dibutyltin bis(acetylacetonate).

7. The organic silicone adhesive according to any one of claims 1 to 5, characterized in that: The mass ratio of the terminal hydroxyl polydimethylsiloxane to the dimethyl silicone oil is 15:1-25:

1.

8. The organic silicone adhesive according to any one of claims 1 to 5, characterized in that: The mass ratio of the surface modified nano calcium carbonate to the alkoxy modified MQ resin is 1.9:1-3.3:

1.

9. A method for preparing the organic silicone adhesive according to any one of claims 1 to 8, characterized in that: include: Stir terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil, surface modified nano calcium carbonate and alkoxy modified MQ resin for 2-4 hours in an environment with a temperature of 100-120° C. and a vacuum degree of less than or equal to -0.095 MPa to obtain a first mixture; Adding a crosslinking agent to the first mixture and stirring for 15-25 minutes to obtain a second mixture; A silane coupling agent and a catalyst are added to the second mixture, and the mixture is stirred for 20-30 minutes in an environment with a vacuum degree of -0.10 MPa to -0.09 MPa to obtain the organic silicone adhesive.

10. A photovoltaic module, characterized in that: It comprises the organic silicone adhesive as described in any one of claims 1 to 8.

Citation Information

Cited By

  • Benzoxazine type adhesive easy to peel after being heated as well as preparation method and use method of benzoxazine type adhesive

    CN120623938A